Interactive effects of rhizospheric soil microbes and litter on the growth of the invasive hyperaccumulator Bidens pilosa in cadmium-contaminated soil - Wang, Xue; Zheng, Wei-Long; Wu, Chun-Lan; Han, Jing-Jing; Xiang, Yu-Peng; Yang, Ming-Lang; He, Peng; Yu, Fei-Hai; Li, Mai-He (Frontiers in Plant Science, 2024)
Both rhizospheric soil microbes and shoot litter input can have profound effects on plant performance; however, their interactive effects on plants in Cd-contaminated soils remain poorly understood. We grew an invasive hyperaccumulator, Bidens pilosa, in sterilized and unsterilized rhizosphere soil without litter or with a low (0.2%, dry weight ratio) or a high amount (1%) of litter from B. pilosa in soil with low (5 mg kg-1) or high (10 mg kg-1) concentrations of Cd. The total, shoot, and root biomass of B. pilosa increased significantly with litter addition, by an average of 27%, 28% and 20%, respectively. The biomass of B. pilosa was significantly lower in unsterilized rhizosphere soil than in sterilized rhizosphere soil, decreasing by 19% for total, 18% for shoot and 24% for root, respectively. Furthermore, the effects of different litter amounts (0.2% vs. 1%) on biomass did not vary in sterilized rhizosphere soils, but significantly varied in unsterilized rhizosphere soils, showing that the biomass was significantly lower with 1% litter addition than with 0.2% litter addition in unsterilized rhizosphere soils, decreasing by 28% for total, 29% for shoot and 21% for root, respectively. Tissue Cd concentrations were significantly higher in highly Cd-contaminated soils (+75% for shoot and +51% for root) than in low Cd-contaminated soils; however, higher tissue Cd concentrations did not cause a significant decrease in the biomass of B. pilosa. Soil fungal communities, particularly the dominant phyla, Ascomycota and Basidiomycota, play crucial roles in modulating the effects of rhizosphere soil microbes and litter on the growth of B. pilosa. Our results suggest that rhizosphere soil microbes and litter interact and affect the growth of B. pilosa: litter addition promoted growth by increasing the abundance of saprotrophs (especially Basidiomycota) and decreasing Cd accumulation in plant tissues, and rhizosphere soil inhibition was associated with a decreased abundance of Basidiomycota. Our findings highlight the importance of the interactive effects of rhizospheric soil microbes and litter on plant growth in Cd-contaminated soils.